Can mobile phones improve nutrition among pastoral communities? Panel data evidence from Northern Kenya - Martin C. Parlasca; Oliver Mußhoff; Matin Qaim (Agricultural Economics, 2020)
The digital revolution and the ongoing dissemination of mobile phones carry several prospects for smallholder farmers in sub-Saharan Africa. Food insecurity and low dietary quality remain major issues among African smallholders. Mobile phones could potentially facilitate access to food markets and thus improve food security and nutrition, but research on such types of effects remains scarce. In this study, we analyze whether mobile phones improve dietary quality among pastoral communities in Northern Kenya. We use six rounds of household panel data covering the period between 2009 and 2015. During this period, mobile phone ownership in the sample increased from less than 30% to more than 70%. Regression models with household fixed effects allow robust estimation while reducing potential issues of unobserved heterogeneity. The estimates show that mobile phone adoption and use are positively and significantly associated with dietary diversity. The effects are particularly large for frequent mobile phone users. We also examine the underlying mechanisms. Mobile phone use improves dietary diversity mainly through better access to purchased foods. These results encourage the promotion of mobile phone technologies as a valuable tool for nutritional improvements, especially in remote rural settings with poor access to food markets.
Keywords: 330; dietary diversity; Kenya; mobile phones; pastoralism